Implementasi Pengunaan Aplikasi Pada Data Kependudukan Dan Surat Menyurat Di Dinas Sosial Kabupaten Batubara - Syafriadi; Alamsyah Putra, Suria (Jurnal Pengabdian Masyarakat Gemilang (JPMG), 2022)
Population data processing application is software that was created to process population data and correspondence entered by the user with the aim of becoming information. This population data processing application is provided complete with software in Microsoft Office that is often used. In its implementation in the workplace, employees are often found who are not familiar with the many facilities provided in the Microsoft Word software. Because so far the employees have not been provided with direct training for the introduction of these functions. Employees of the Social Service Office of Batubara Regency do not use the software technology in computer programs, especially population data processing applications and correspondence. For this reason, they need encouragement to improve their ability to operate office software, especially Microsoft Word software in processing data and information. This community service activity aims to improve the ability of Social Service Employees to use Microsoft Office properly and improve skills in performing services and work in their workplace. The training method is discussion and interactive in conveying knowledge to training participants. This training provides knowledge that can be implemented in the workplace of the trainees which is very helpful in completing tasks in their agencies. The results of the assessment that in participating in this training the participants were able to understand the training material based on the exercises and examples provided by the resource persons